A legal analysis of community rejection of the landfill designation policy in Bangkonol village, Koroncong district, from a criminal law perspective - Enjum Jumhana; Sanniki Setia Perdani; Faturohman Faturohman; Muhammad Deni Latiful Khoir; Wahyudi Wahyudi (Institute Of computer Science (IOCS), 2026)
This study aims to analyze the legal aspects of public rejection of the policy of establishing a Final Disposal Site (TPA) for waste in Bangkonol Village, Koroncong District, from a criminal law perspective. Public rejection arose in response to concerns about environmental and health impacts, as well as the lack of public involvement in the policy-making process. The research method used is normative juridical with a statutory regulatory approach and a case study approach, supported by empirical data as a complement. The results of the study indicate that public rejection is essentially a form of public participation guaranteed by the legal system, but in practice it has the potential to result in criminal legal consequences if carried out in unlawful ways, such as destroying public facilities, obstructing government projects, or other anarchic actions. On the other hand, the government also has an obligation to ensure that the policies adopted have met the principles of legality, transparency, and justice, including the implementation of an environmental impact analysis (AMDAL) and outreach to affected communities. From a criminal law perspective, it is important to assess the elements of fault (mens rea) and unlawful acts (actus reus) in every act of rejection. Therefore, a balanced approach between law enforcement and the protection of community rights is needed to prevent excessive criminalization of citizens and encourage dialogical and just conflict resolution. This research is expected to contribute to the development of more responsive public policies oriented toward community interests.